Using SRSD to Improve the Fraction Computations of Students With and At-Risk for EBD. (February 2021) - Losinski, Mickey; Ennis, Robin Parks; Shaw, Ashley
This article provides results from a study examining the impact of a self-regulated strategy development (SRSD) intervention on the fraction calculations of three Grade 5 male students with or at-risk for emotional or behavioral disorders using a multiple-baseline across students, single-case design. The teacher-led SRSD Fractions intervention addressed adding and subtracting fractions with unlike denominators using the FILMS (Find the denominator, Identify the multiples, Locate the least common multiple, Multiply to make new fractions, Solve the problem) strategy. Results of fraction probes are reported along with a discussion of the study with respect to the research question posed, limitations, and future directions for research.